EFEKTIVITAS PENGUJIAN KUAT TEKAN BETON PADA SPUN PILE DENGAN METODE CORE DRILL, HAMMER TEST, DAN COMPRESSIVE STRENGTH TEST DI PT JAYA BETON INDONESIA - Zulfikar, Ahmad Rafly (Jurnal Vokasi Teknik Sipil, 2023)
Testing the concrete structure after the concrete has hardened is to determine whether the concrete structure is suitable for use according to the planned quality. Concrete quality testing is carried out without damaging the concrete. This study aims to find out how to identify the quality of spun pile, to know the differences in methods and results between the core drilling test, compressive strength test, and concrete hammer test, and to find out which method is more effective for identifying the compressive strength quality of spun pile. The method used to determine the capacity and structural strength of spun pile using 3 test methods, namely the Core Drill Test, Schmidt Hammer Test, and Compressive Strength Test methods are used as an alternative in determining the compressive strength value of spun pile. The results of the concrete compressive strength test on spun pile using the Core Drill Test, Schmidt Hammer Test, and Compressive Strength Test methods have fulfilled the requirements. The results of the compressive strength test using the core drill test method obtained an average yield of 50.98 Mpa for spun pile fc 45 and 55.83 Mpa for spun pile fc 50. From the results of the Schmidt hammer test it indicates that the coefficient of variation (KV) of the overall spun pile samples tested ranged from 3.19% -4.72%. The Compressive Strength Test obtained an average compressive strength of spun pile fc 45 of 57.22 MPa for a 28 day old concrete sample. As for the spun pile fc 50, it obtained an average yield of 64.35 MPa for a concrete sample aged 28 days. Based on data analysis, the effectiveness of testing the compressive strength of concrete can be concluded that the Core Drill Test is very effective in testing the compressive strength of concrete.